2008
DOI: 10.1128/jvi.02161-07
|View full text |Cite
|
Sign up to set email alerts
|

4E10-Resistant Variants in a Human Immunodeficiency Virus Type 1 Subtype C-Infected Individual with an Anti-Membrane-Proximal External Region-Neutralizing Antibody Response

Abstract: The broadly neutralizing monoclonal antibody (MAb) 4E10 recognizes a linear epitope in the C terminus of the membrane-proximal external region (MPER) of gp41. This epitope is particularly attractive for vaccine design because it is highly conserved among human immunodeficiency virus type 1 (HIV-1) strains and neutralization escape in vivo has not been observed. Multiple env genes were cloned from an HIV-1 subtype C virus isolated from a 7-year-old perinatally infected child who had anti-MPER neutralizing antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 38 publications
3
58
0
Order By: Relevance
“…The observation that CAP256 neutralization sensitivity is determined by the presence of crucial residues within the V2 epitope but also by the length of the adjacent V1 loop was not unexpected. Indeed, this is similar to 4E10, where the sensitivity of viruses containing the intact epitope in the MPER may be modulated by changes elsewhere in the envelope (13 (40), as well as affecting the sensitivity of heterologous viruses to such specificities. Unlike the V1 loop, which is likely to be structurally disordered and is very variable in length, the V2 loop contains a number of subdomains that are very conserved across all subtypes and shows a greater constraint on the minimum length tolerated (48).…”
Section: Discussionmentioning
confidence: 74%
“…The observation that CAP256 neutralization sensitivity is determined by the presence of crucial residues within the V2 epitope but also by the length of the adjacent V1 loop was not unexpected. Indeed, this is similar to 4E10, where the sensitivity of viruses containing the intact epitope in the MPER may be modulated by changes elsewhere in the envelope (13 (40), as well as affecting the sensitivity of heterologous viruses to such specificities. Unlike the V1 loop, which is likely to be structurally disordered and is very variable in length, the V2 loop contains a number of subdomains that are very conserved across all subtypes and shows a greater constraint on the minimum length tolerated (48).…”
Section: Discussionmentioning
confidence: 74%
“…2A). HIV-2 KR.X7 was less infectious than HIV-2 KR.X4 , although still within a range observed for primary HIV-2 and HIV-1 strains and previously described HIV-2/HIV-1 chimeras (18,34,49). The V3 chimeric viruses HIV-2 KR.X7 YU2 V3, HIV-2 KR.X7 Ccon V3, and HIV-2 KR.X7 MN V3 were infectious and again exhibited a broad range in infectivity compared with the isogenic HIV-2 KR.X7 scaffold and the HIV-2 KR.X4 parental strain.…”
Section: Constructionmentioning
confidence: 99%
“…Previously, we along with others have demonstrated that HIV-2 Env could be used as a scaffold to present HIV-1 MPER and CD4i epitopes in the context of a functional glycoprotein and that such viruses could serve as sensitive and specific probes for HIV-1-elicited epitope-specific NAbs (18,19,34,61,102 In the present study, we focused on HIV-1 V3, which continues to attract substantial attention as a target of NAbs (2,54,72,74,76,99,107). Mamounas and colleagues first demonstrated that a chimeric virus containing an HIV-2 backbone and an HIV-1 MN V3 loop was capable of infecting human T cells and showed susceptibility to HIV-1 V3-specific antiserum (64).…”
Section: Discussionmentioning
confidence: 99%
“…Co-administration of 4E10 and 2F5 results in a synergistic neutralizing effect in vitro (Zwick et al, 2001b). To note, substitutions in the MPER contributed to the resistance to 4E10 (Gray et al, 2008;Nakamura et al, 2010). The safety and tolerability of 4E10 for clinical use have also been confirmed by a phase 2 clinical study (Joos et al, 2006).…”
Section: Passive Immunization Using Neutralizing Antibodiesmentioning
confidence: 60%